Review of Chinese Empoasca Walsh (Hemiptera: Cicadellidae), with description of seven new species and some new Chinese records - Liu, Yang; Qin, Dao-Zheng; Fletcher, Murray J.; Zhang, Ya-Lin (Zootaxa, 2011)
Seven new species of Empoasca (Empoasca) Walsh, 1862 are described and illustrated. Five of the new species belong to the Empoasca warchalowskii group: Empoasca (Empoasca) longa Zhang & Liu, Empoasca (Empoasca) megalophylla Qin & Liu, Empoasca (Empoasca) paragucia Fletcher & Liu, Empoasca (Empoasca) undulata Zhang & Liu, Empoasca (Empoasca) vickiae Liu, spp. nov. The other two new species cannot be placed into a species group: Empoasca (Empoas- ca) dendritica Qin & Liu and Empoasca (Empoasca) polyprocessa Fletcher & Liu, spp. nov. An additional 15 species and the subgenus Empoasca (Livasca) Dworakowska & Viraktamath, 1978 are recorded for the first time from China.